SM2CL Model Innovation: Biology Learning Strategy to Sharpen Students' Critical Thinking - Muhammad Sultani Taufik; Joan S Awingan; Feona S Carollo (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the influence of the Synectics, Mind Maps, and Cooperative Learning (SM2CL) learning models on students' critical thinking skills in biology subjects. Methodology: This study is a quasi-experimental study with a pretest-posttest control group design. The sampling technique used was total sampling with 47 students as samples. The research instruments consisted of essay tests and critical thinking scale questionnaires. Data were analyzed using descriptive and inferential statistics with normality tests, homogeneity tests, and t-tests using SPSS software version 24. Main Findings: The Synectics, Mind Maps, and Cooperative Learning (SM2CL) learning model significantly improves students' critical thinking skills. The t-test results showed a significant difference between the experimental class and the control class, with a higher increase in post-test scores in the experimental class. The analysis data showed that the SM2CL model was effective in improving students' conceptual understanding and critical thinking skills in Biology subjects. Novelty/Originality of this study: This study combines three learning models Synectics, Mind Maps, and Cooperative Learning (SM2CL), as an innovative approach to improve students' critical thinking in Biology. This study expands the understanding of the effectiveness of collaborative and visual methods in learning, and provides new insights into the application of integrated learning strategies in improving the quality of education.